Exploring Platform Choices in Enhancing English Speaking Skills: A Case Study in Jambi Province - Winny Berliana; Rojab Siti Rodliyah; Bachrudin Musthafa (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study investigates the alignment between teachers’ selected digital platforms and students’ platform preferences in supporting English speaking practice in the EFL context of Jambi Province, Indonesia. Despite the increasing integration of digital tools in language learning, limited research has explored how mismatches between teacher choices and student preferences influence speaking engagement.A qualitative case study design was employed involving 30 students and 2 English teachers from two secondary schools selected through purposive sampling. Data were collected through semi-structured interviews and supported by questionnaires for triangulation. The data were analyzed thematically using Oxford’s (1990) language learning strategies framework.The findings reveal that WhatsApp and YouTube were the most frequently used platforms due to their accessibility and ease of use. However, students showed a stronger preference for Instagram, which they perceived as more engaging and less anxiety-inducing for speaking practice. While partial alignment existed in the use of familiar platforms, a notable misalignment emerged in platform preference, potentially limiting students’ engagement and opportunities for meaningful speaking practice.The study concludes that effective integration of digital platforms in EFL speaking instruction requires not only consideration of accessibility and teacher manageability but also alignment with students’ preferences. Incorporating student-preferred platforms in a structured and pedagogically sound manner may enhance engagement and support more meaningful speaking practice, particularly in contexts with infrastructural constraints.